[PP.16.21] A COMPARATIVE STUDY ON SKIN AND PLASMA ADVANCED GLYCATION END PRODUCTS AND THEIR ASSOCIATIONS WITH ARTERIAL STIFFNESS IN UNTREATED CHINESE. (September 2016) - Liu, C.; Huang, Q.; Li, Y.; Wang, J.
Abstract : Objective: The aim of our study is to compare skin and plasma advanced glycation end products (AGEs), with particular focus on their levels in men and in the presence of hypertension or diabetes and prediabetes and their associations with arterial stiffness. Design and method: Consecutive patients who were referred for ambulatory blood pressure monitoring in Ruijin Hospital, Shanghai, China were recruited if they were not taking antihypertensive medication for at least 2 weeks. Skin AGEs accumulation was measured on both forearms using the skin Autofluorescence Reader (AFR, The Netherlands) and expressed in arbitrary unit in the range from 0 to 25. Plasma AGEs concentration was measured by the enzyme-linked immunosorbent assay kits (Cusabio Biotech, Wuhan, China) and logarithmically transformed for statistical analysis. Arterial stiffness was assessed by carotid-femoral pulse wave velocity (cfPWV) using the SphygmoCor system (Sydney, Australia). Results: The 161 participants had a mean age, skin and plasma AGEs and cfPWV of 51.5 years, 1.88 and 3.93 ug/ml and 8.1 m/s, respectively. Skin and plasma AGEs were not significantly correlated (P = 0.59). Nonetheless, both were significantly (P < = 0.02) higher in men (n = 71, 1.97 and 5.75 ug/ml, respectively) than women (n = 90, 1.81 and 2.91 ug/ml, respectively) and in diabetic or prediabetic (n = 26, 2.04 and 5.54 ug/ml, respectively) than nondiabetic subjects (n = 135, 1.85 and 3.67 ug/ml, respectively), but not in hypertensive (n = 57) than normotensive subjects (n = 104, P > = 0.71). In adjusted analyses, plasma but not skin AGEs were significantly associated with cfPWV in all subjects (r = 0.18; P = 0.03 and r = 0.03; P = 0.74, respectively) and in subgroups of men, diabetes and prediabetes and hypertension (r = 0.20 to 0.38; P < = 0.054 and r = 0.05 to 0.09; P > = 0.48, respectively). Conclusions: Although skin and plasma AGEs were similarly associated with gender and diabetes or prediabetes, they might measure something different and have different clinical relevance, such as for arterial stiffness.